Gambaran Efektifitas Konseling Sufistik untuk Meningkatkan Motivasi Sembuh Pasien di RSU Lirboyo Kota Kediri - Fitriah, Lailatul; Triana, Renny (Happiness: Journal of Psychology and Islamic Science, 2022)
Motivation to recover is the most needed thing for patients, such as having a positive attitude towards oneself, goal-oriented, and strength and drive in achieving goals. One of the things that can increase patient motivation to recover is by providing Sufistic counseling. The purpose of this study was to determine the effectiveness of Sufistic counseling to increase the motivation to recover of inpatients at Lirboyo General Hospital. The research method used observation and interviews. The samples of this study were 3 inpatients at Lirboyo General Hospital who had stayed more than one day. The results showed that patients who were given Sufistic counseling experienced an increase in motivation to recover. The results of the interview explained that the patient with a stroke diagnosis, felt calmer, happier and more enthusiastic because he had high hopes and desires to be healthy again soon. The patient with a diagnosis of diabetes felt that the burden of thoughts and feelings that haunted him every day could gradually be released because he had surrendered his problems to God. So that he feels calmer. Patient with a diagnosis of Dyspepsia felt more energized because he already had the belief that Allah would soon provide healing because he had made efforts and was patient. This research is expected as a source of information in order to improve health care efforts by providing Sufistic counseling services to patients. The importance of Sufistic counseling for patients is to fulfill spiritual needs in the field of medicine not for the purpose of changing the patient's belief in his religion but to generate spiritual strength in the face of suffering from illness or disturbances in his health and generate a spirit of motivation to recover.